Short-Term and Long-Term Effects of the Islamic Bank Financing in Construction Sector on GDP in Indonesia - Eko Fajar Cahyono; Nur Syazwani Mazlan; Mohd Naseem Niaz Ahmad; Wan Azman Saini Wan Ngah; Azali Mohamed (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 21 Issue 2 Page (77-101)